Oxazolidinone-based allosteric modulators of mGluR5: Defining molecular switches to create a pharmacological tool box. Issue 17 (1st September 2016) - Huang, Hong; Degnan, Andrew P.; Balakrishnan, Anand; Easton, Amy; Gulianello, Michael; Huang, Yanling; Matchett, Michele; Mattson, Gail; Miller, Regina; Santone, Kenneth S.; Senapati, Arun; Shields, Eric E.; et al.
Graphical abstract: Abstract: Herein we describe the structure activity relationships uncovered in the pursuit of an mGluR5 positive allosteric modulator (PAM) for the treatment of schizophrenia. It was discovered that certain modifications of an oxazolidinone-based chemotype afforded predictable changes in the pharmacological profile to give analogs with a wide range of functional activities. The discovery of potent silent allosteric modulators (SAMs) allowed interrogation of the mechanism-based liabilities associated with mGluR5 activation and drove our medicinal chemistry effort toward the discovery of low efficacy (fold shift) PAMs devoid of agonist activity. This work resulted in the identification of dipyridyl22 (BMS-952048), a compound with a favorable free fraction, efficacy in a rodent-based cognition model, and low potential for convulsions in mouse.